The effects of dietary n-3 series fatty acid on the fatty acid composition, cholesterol and fat-soluble vitamins of pleopodal eggs and stage 1 juveniles in a freshwater crayfish, Astacus leptodactylus (Eschscholtz) - Harlioglu, Muzaffer Mustafa; Koprucu, Kenan; Harlioglu, Ayse Gul; Yilmaz, Okkes; Aydin, Sevinc; Yonar, Serpil Mise; Ozcan, Sinan (Elsevier, 2012)
To investigate the effects of dietary n-3 series fatty acid levels on the fatty acid composition, cholesterol and fat-soluble vitamins of pleopodal eggs and stage 1 juveniles in Astacus leptodactylus one control (D1) and three experimental diets (D2, D3 and D4) were prepared. n-3 series fatty acids were not included in the control diet, however, D2, D3 and D4 diets were supplemented with n-3 series fatty acids (n-3 series fatty acid concentrated from anchovy oil and contains 54.3% eicosapentaenoic acid, 37.1% docosahexaenoic acid and 8.6% other n-3 series fatty acid; docosapentaenoic, linolenic, stearidonic acid) at 1%, 2% and 3% level, respectively. Crayfish were fed these isonitrogenous (35% crude protein) and isocaloric (3600 kcal kg(-1) gross energy) formulated diets for 251 days. The results showed that the dietary n-3 series fatty acids improved the chemical quality of pleopodal eggs and stage 1 juveniles (i.e., fatty acid composition, cholesterol and fat-soluble vitamin content). The results also showed that the fatty acid profiles of pleopodal eggs and juveniles were similar to the fatty acid profiles of D1, D2, D3 and D4. In general, increasing concentrations of dietary n-3 series fatty acids lowered the deposition of linoleic acid (18:2n-6) and total n-6 PUFA (polyunsaturated fatty acids), but simultaneously improved the deposition of linolenic acid (18:3n-3), stearidonic acid (18:4n-3), eicosapentaenoic acid (20:5n-3), docosapentaenoic acid (22: 5n-3), docosahexaenoic acid (22:6n-3) and total n-3 PUFA in the eggs and juveniles. However, the levels of cholesterol and fat-soluble vitamins in pleopodal eggs and stage 1 juveniles were unaffected by the dietary n-3 series fatty acids (except delta-tocopherol, vitamin K-2 and cholesterol levels of stage 1 juveniles). The best chemical quality in eggs and juveniles was obtained from the crayfish fed D4. In conclusion, n-3 series fatty acid concentrations in broodstock diets significantly improved the quality of pleopodal eggs and stage 1 juveniles in A. leptodactylus. (C) 2012 Elsevier B. V. All rights reserved.
Keywords: Astacus leptodactylus; Cholesterol; Pleopodal egg; Fat-soluble vitamin; Fatty acid; Juvenile